PENGARUH Trichoderma harzianum SEBAGAI AGENS HAYATI UNTUK PERTUMBUHAN DAN KESEHATAN BIBIT VANILI (Vanilla planifolia) TERHADAP Fusarium oxysporum - Rismawati; Pramono Hadi; Shalahudin Mukti Prabowo (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
Research on "the effect of Trichoderma harzianum as a biological agent for the growth and health of vanilla (Vanilla planifolia) seedlings against Fusarium oxysporum". Starting September-November 2020, in Klodran Village, Colomadu District, Karanganyar Regency, Central Java Province. The research used factorial method with the basic pattern of Completely Randomized Design (CRD), with 2 treatment factors and repeated 3 times. Factor 1). Trichoderma harzianum treatment frequency 3 levels, namely: 4 days (F1), 7 days (F2) and 10 days (F3). Factor 2) Trichoderma harzianum concentration treatment with three levels, namely: Trichoderma harzianum concentration 1 ml / l water (K1), Trichoderma harzianum concentration 5 ml / l water (K2) and Trichoderma harzianum concentration 9 ml / l water (K3). Data analysis with F-test for analysis of variance, Duncan's Multiple Range Test (DMRT) if significantly different. The frequency of Trichoderma harzianum application had a very significant effect on shoot length, number of leaves, plant wet weight, plant dry weight and disease intensity. The best treatment for growth and health of vanilla plants was given Trichoderma harzianum, the frequency of Trichoderma harzianum every 4 days. The concentration of Trichoderma harzianum had a very significant effect on shoot length, number of leaves and disease intensity, fresh and dry plant weight. The growth and health of vanilla plants, the concentration of Trichoderma harzianum that best matches the Trichoderma harzianum concentration of 9 ml / l of water